The Effects of Age, from Young to Middle Adulthood, and Gender on Resting State Functional Connectivity of the Dopaminergic Midbrain - Peterson, Andrew C.; Zhang, Sheng; Hu, Sien; Chao, Herta H.; Li, Chiang-shan R. (Frontiers in Human Neuroscience, 2017)
Dysfunction of the dopaminergic ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) is implicated in psychiatric disorders including attention-deficit/ hyperactivity disorder (ADHD), addiction, schizophrenia and movement disorders such as Parkinson’s disease. Although the prevalence of these disorders varies by age and sex, the underlying neural mechanism is not well understood. The objective of this study was to delineate the distinct resting state functional connectivity (rsFC) of the VTA and SNc and examine the effects of age, from young to middle-adulthood, and sex on the rsFC of these two dopaminergic structures in a data set of 250 healthy adults (18-49 years of age, 104 men). Using blood oxygenation level dependent (BOLD) signals we compared the time course of the VTA and SNc to the time courses of all other brain voxels. At a corrected threshold, paired t test showed stronger VTA connectivity to bilateral angular gyrus and superior/middle and orbital frontal regions and stronger SNc connectivity to the insula, thalamus, parahippocampal gyrus and amygdala. Compared to women, men showed a stronger VTA/SNc connectivity to the left posterior orbital gyrus. In linear regressions, men but not women showed age-related changes in VTA/SNc connectivity to a number of cortical and cerebellar regions. Supporting shared but also distinct cerebral rsFC of the VTA and SNc and gender differences in age-related changes from young and middle adulthood in VTA/SNc connectivity, these new findings help advance our understanding of the neural bases of many neuropsychiatric illnesses that implicate the dopaminergic systems.